PREDIKSI LAMA KEMATIAN BERDASARKAN KEBERADAAN SERANGGA GENUS LUCILIA (CALLIPHORIDAE) PADA BANGKAI MENCIT (Mus musculus) DI LOKASI HUTAN MANGROVE - Laksmita, Ayu Saka; Watiniasih, Ni Luh; Junitha, I Ketut (Jurnal Biologi Udayana; Vol 17 No 1 (2013): Jurnal Biologi, 2013)
Normal 0 false false false EN-US X-NONE X-NONE This study aimed to investigate the presence of insects on mice carcasses in mangrove forest, the chronology of the insect presence and growth phase of the insects on estimating the time of death of the animal for the beneficial of forensic study. Collected insects were identified at The Laboratory of Animal Taxonomy and The Laboratory of Ecology, Department of Biology, Udayana University. The samples were divided into two based on the study areas: dry and watered areas. Five mice carcasses in three different spot were laid on each dry area. The data collected were analyzed descriptively. The differences of insect growths from egg to pupae and also the ex-pupae found on carcasses could be used to estimated the time of death of an animal.
Keywords: forensic entomology, Calliphoridae, carcass